Development and validation of a UPLC-MS/MS method for the quantification of parsaclisib and its application to pharmacokinetics and metabolic stability studies - Chenjian Zhou; Peiqi Wang; Jie Chen; Hualu Wu; Yige Yu (BMC Chemistry)
Abstract Parsaclisib is a novel, potent, highly selective, next-generation oral inhibitor of phosphatidylinositol 3-kinase δ (PI3Kδ) for patients with relapsed or refractory B-cell malignancies. However, there is no accurate and rapid method for the determination of parsaclisib. The aim of this study was to establish a rapid, specific and reliable ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) method for the determination of parsaclisib, and to investigate in vitro metabolic stability using rat liver microsomes (RLMs) and in vivo pharmacokinetics in rats. Parsaclisib was detected by gradient elution on an Acquity UPLC BEH C18 column (2.1 mm × 50 mm, 1.7 μm) using acetonitrile and 0.1% formic acid as mobile phases, and pilaralisib was used as an internal standard (IS). Selective reaction monitoring (SRM) was used for detection. The method showed acceptable intra- and inter-day precision (< 8.6%) and accuracy (2.0–14.9%). The stability of the test samples was reliable during the analysis. In addition, the recoveries and matrix effects of the samples were within acceptable limits and were stable during storage and determination in rat plasma. The pharmacokinetic trend of parsaclisib in rats was also investigated by this newly developed assay after gavage administration of 2.0 mg/kg parsaclisib. Finally, in vitro results showed that parsaclisib had a slow intrinsic clearance (Clint) value of 2.4 µL/min/mg protein with a half-life (t1/2) value of 571.3 min. These findings theoretically supported the potential metabolism of parsaclisib in vivo.